Colorimetric analysis: A new strategy to improve ratiometric temperature sensing performance of lanthanide benzenedicarboxylates - Kitt Panyarat (2019)
© 2019 Elsevier B.V. A series of monometallic [Ln 2 (BDC) 3 (DMF) 2 (H 2 O) 2 ] n (Ln = Eu III , Gd III , Tb III ; H 2 BDC = benzene-1,4-dicarboxylic acid; DMF = dimethylformamide) and the lanthanide luminophores-loaded [Ln x Gd 2-x (BDC) 3 (DMF) 2 (H 2 O) 2 ] n (Ln = Eu III and Tb III ) were synthesized and used in photoluminescent study. The dependence of emitting colors of [Ln x Gd 2-x (BDC) 3 (DMF) 2 (H 2 O) 2 ] n on the luminophore contents is reported and discussed based on the sensitization efficiency of BDC 2− antenna. On the basis of an explicit change in the emitting colors of [Eu x Gd 2-x (BDC) 3 (DMF) 2 (H 2 O) 2 ] n , colorimetric analysis has been introduced as a new and effective strategy to establish ratiometric-thermometric parameters. Within the sRGB and CIE XYZ color matching systems, the temperature-dependent ratiometric-thermometric parameters could be derived from both x/(x+y) and R/(R+G) over 303–348 K covering physiological temperatures. Temperature resolution in term of standard deviation of the measurements, repeatability and relative sensitivity of the successive measurements have been evaluated and are reported.